Desempenho térmico de fachada ventilada - Biazus, Ramom Felipe (Universidade do Vale do Rio dos Sinos, 2024)
The search for constructive solutions that meet thermal comfort requirements has become increasingly relevant in the field of civil construction. In this context, the ventilated facade has garnered interest as an efficient alternative for controlling the thermal performance of buildings. A ventilated facade is an external cladding system that allows air circulation between the outer layer and the support wall, contributing to the thermal control of the internal environment. The thermal performance of a ventilated facade is influenced by various factors, such as the composition and thickness of the materials used, the geometry of the ventilated air chamber, and the overall system configuration. Understanding how these factors interact, and impact thermal performance is fundamental for designing efficient ventilated facades. The objective of this study is to analyze the thermal performance of ventilated facades, investigating the relationship between variables and providing insights for the development of more efficient constructive solutions. For this purpose, computational simulations were conducted considering different configurations of ventilated facades, varying parameters such as air chamber thickness, cladding materials, and spacings. Understanding the mechanisms involved in the thermal performance of ventilated facades will allow for the appropriate selection of materials and system configuration, aiming to make the best use of the thermal properties offered by this type of facade. Additionally, the knowledge gained can contribute to the optimization of projects and the creation of more comfortable and sustainable buildings, promoting the quality of life for occupants and reducing energy consumption.
Keywords: Fachada ventilada; Desempenho térmico; Simulação computacional; Ventilated facade; Thermal performance; Computational simulation; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo